200 years after the birth of the Peruvian Republic (1822-2022) - MERA AVALOS , ARNALDO (2023)
This article seeks to clarify in a documentary way when exactly the Republic was born in our country, day, month and year; which, as we know, was part of a process that ideologically can be traced back to the Praise of the Count of Vista Florida to Viceroy Jauregui and the Letter to the Spanish Americans of Juan Pablo Vizcardo Guzmán and politically to the Provisional Regulations issued on February 12, 1821. and the Provisional Statute of October 8, 1821, both given by General José de San Martin who, upon leaving Peru, left the Constituent Congress installed, which, after almost three months of operation, dictated the Bases of the Political Constitution of Peru on December 16. of 1822 promulgated by the Governing Board the following day; With this we seek to correct the error that Mr. Jorge Basadre made in the first chapter of the first volume of the History of the Republic of Peru by indicating as such on December 19 but that the teacher José Agustín de la Puente Candamo in the sixth volume of The General History of Peru clarifies and states that it was December 17, 1822